2017
DOI: 10.1016/j.cbpa.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomally synthesized and post-translationally modified peptide natural product discovery in the genomic era

Abstract: In the past 15 years, the cost of sequencing a genome has plummeted. Consequently, the number of sequenced bacterial genomes has exponentially increased, and methods for natural product discovery have evolved rapidly to take advantage of the wealth of genomic data. This review highlights applications of genome mining software to compare and organize large-scale data sets and methods for identifying unique biosynthetic pathways amongst the thousands of ribosomally synthesized and post-translationally modified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
118
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 55 publications
0
118
0
Order By: Relevance
“…1 Recent genome sequencing efforts have revealed that RiPPs form a large natural product class produced by all domains of life. 2,3 In general, RiPP biosynthesis commences with the post-translational modification (PTM) of a precursor peptide, typically consisting of N -terminal leader and C -terminal core regions. 14 The RiPP precursor peptide gene is often encoded adjacent to other genes responsible for regulation, biosynthesis, and export.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent genome sequencing efforts have revealed that RiPPs form a large natural product class produced by all domains of life. 2,3 In general, RiPP biosynthesis commences with the post-translational modification (PTM) of a precursor peptide, typically consisting of N -terminal leader and C -terminal core regions. 14 The RiPP precursor peptide gene is often encoded adjacent to other genes responsible for regulation, biosynthesis, and export.…”
Section: Introductionmentioning
confidence: 99%
“…In some rare cases, a leader peptide is not attached at the N terminus of the core peptide, but rather at the C terminus, which is hence termed a follower peptide . RiPPs are found in all three domains of life and have highly diverse biological activities, representing a promising source for the development of novel drug leads .…”
mentioning
confidence: 99%
“…The growing numbers of natural bioactive peptide structures, resulting from the genomic era discoveries, continue to inspire development of new molecular tools and peptide design. If the past ∼35 years' growth trends continue, we anticipate seeing many more and interesting naturally occurring and designed peptide/protein structures in the PDB and CSD.…”
Section: Discussionmentioning
confidence: 99%
“…If the past ∼35 years' growth trends continue, we anticipate seeing many more and interesting naturally occurring and designed peptide/protein structures in the PDB and CSD. Although ribosomal biosynthetic machinery does not naturally support incorporation of amino acids with modified backbones, a recent study suggests that by using an editing‐deficient valine‐tRNA synthetase, the ribosomal translation machinery incorporated eleven non‐coded amino acids in proteins—including α,α‐disubstituted, and cyclic β‐amino acids . This and similar systems may be harnessed to design conformationally constrained peptides with applications in basic science, biotechnology, bio‐engineering, and for biomedical applications …”
Section: Discussionmentioning
confidence: 99%